INTERACTIONS BETWEEN LEGAL SYSTEMS IN THE JUDICIAL PROCESS OF KENDENG CASE (A CRITICAL ANALYSIS OF ACCESS TO JUSTICE) - Wahyu Nugroho (Diponegoro Law Review, 2018)
The Indonesian state has the characteristic of legal system plurality in a national legal system, it is interesting to be observed from law making, licencing, law implementation, to judiciary process. State organizers in the context of government (executive power) as the licensors of business activities and the judiciary (judicial power) State Administration, as absolute competence over the objects of environmental administration disputes require optical and comprehensive holistic understanding, amidst the very diverse conditions of the legal system (legal pluralism) and a pluralistic society to be bound in a single national legal system (unification). The problem formulation in this paper is: (1) How is the interaction of continental European legal system and customary law system on kendeng case in the tiered judicial process? And (2) how does the interaction affect the legal system on the judge's mindset over environmental permit disputes objects? In relation to executive power as a licensor, the involvement of the public in the process of publishing environmental documents becomes a very important matter. Kendeng Community of Rembang Regency Central Java Province is fighting for its rights and various access to justice, finally choosing the judicial route as the main tool against the state, namely the State Administrative Court (PTUN) Semarang, High Administrative Court (PT TUN) Surabaya, Until the most recent legal remedy in the judicial system in Indonesia, namely the Review Supreme of Court. In this paper, it shows the interaction between the legal system, the continental European legal system and the customary law system in the process of tiered justice as an access to justice for the kendeng mountain community.